2010
DOI: 10.1063/1.3369584
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastable platform for the study of single-atom chains

Abstract: Bond length and electric current oscillation of long linear carbon chains: Density functional theory, MpB model, and quantum spin transport studies The increase in conductance of a gold single atom chain during elastic elongation J. Appl. Phys. 113, 054316 (2013); 10.1063/1.4790379Identification of the atomic scale structures of the gold-thiol interfaces of molecular nanowires by inelastic tunneling spectroscopyWe describe a surface probe instrument capable of sustaining single atomic bond junctions in the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Definitive tests of this connection require quantum-mechanics-based simulations of electron transport within these deformed nanowires and direct comparison with experimental conductance measurements obtained under very similar conditions. 61 It is also important to note that a recent theoretical study by Ke et al 45 showed that simple rotational deformations of an infinite length, zigzagged SAC with constant lattice parameter lead to pronounced changes in the band structure and the opening and closing of a large band gap. Our findings confirm this dependence of the gap on the rotational arrangement of SAC atoms: using structure C in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitive tests of this connection require quantum-mechanics-based simulations of electron transport within these deformed nanowires and direct comparison with experimental conductance measurements obtained under very similar conditions. 61 It is also important to note that a recent theoretical study by Ke et al 45 showed that simple rotational deformations of an infinite length, zigzagged SAC with constant lattice parameter lead to pronounced changes in the band structure and the opening and closing of a large band gap. Our findings confirm this dependence of the gap on the rotational arrangement of SAC atoms: using structure C in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…All of these findings agree with experimental structural observations, 19 as well as with measures of conductance for Au NWs, where very similar plateaus for the quantum conductance are found before the single atom contact is broken, and after it has been broken and reformed again. 61 Lastly, electronic properties of all accessible intermediate structures were computed, and the opening of a small gap ͑about 0.4 eV͒ was found when a small amount of the previously reported 46 ZZ3 + 5 structure developed during elongation. This is a much smaller gap than that found for the ideal, infinite ZZ3 + 5 structure ͑1.3 eV͒, 46 but it was obtained using much more realistic structural and elastic strain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanical properties and the mechanisms that control the conductance in atomic-scale wires is important both from a basic science standpoint and for applications in nanoelectronics and nano-devices. Numerous experimental studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] have been conducted to characterize the mechanical properties and the conductance of silver nanowires during elongation. In these experimental systems, the silver NW is elongated and thinned down to a single atom chain (SAC) in a high vacuum chamber, at ≈4 K. During wire thinning, the conductance is continuously 1 On sabbatical leave from the Nuclear Research Center Negev.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanically controlled breakjunctions (MCBJs) [11] are perhaps the most popular method for achieving the required atomic scale structures, and allow quantized conduction to be observed even at room temperature, but typical lifetimes are only milliseconds. [11,12] The behaviour of MCBJs can sometimes be emulated via electromigration processes in metallic devices, [13] but in many cases quantization is not observed. [14] We randomly deposit pre-formed 7nm tin clusters between pairs of electrical contacts.…”
mentioning
confidence: 99%